Stereotyping - Predispositions, activations and applications in cross-cultural service interactions: Views from service providers in Malaysia - Cheok, Jason *; Aleti, T; Hede, A. M. (Sage Publications, 2016)
The aim of the article was to explore for stereotyping patterns in crosscultural service interactions. This research was set within the context of luxury hotel in Malaysia, where most of the service providers are non-Western. In-depth interviews and written diaries were used to develop deep narratives for the patterns of stereotyping adopted by the service providers. Predispositions, activations and applications of stereotypes were examined considering implicit theory and power distance. Associations between the service providers’ culture and position and their tendency to activate and apply stereotypes were found. The findings highlight the increasing complexity in cross-cultural service interactions within the South East Asian region. This study provides management with insights into service interactions in the contemporary context of Asia, where socio/economic and cultural boundaries are blurring. Practical and theoretical recommendations are made for both management and further academic research on this issue, which has potential to influence guest satisfaction and ultimately business viability